2017
DOI: 10.21522/tijar.2014.04.01.art003
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Attitude and Environmental Behavior of Catholic Colleges’ Employees in Ilocos Sur, Philippines

Abstract: The study was intended to measure the understanding and attitudes of employees of Catholic Colleges in Ilocos Sur Province toward the environment and how such attitudes affect their behavior toward the environment. It was found that overall the employees were not certain related to their attitudes toward the environment and such ambivalent attitudes affect their behavior toward the environment. The study concludes that such ambivalent attitudes are caused by lack of understanding about environmental ethics. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…Therefore, stakeholders should also carry out activities that can increase concern for the environment among campus students. Furman [37] states that elements of concern can be nurtured through knowledge, such as talks on the importance of anti-littering behavior on ecosystem quality; conduct recycling programs by placing recycling bins in places easily accessible by students; showing video footage of environmental quality and its effects that can increase students' level of concern; involving students in program cleaning activities in institutional areas; training or seminar [38]; etc.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, stakeholders should also carry out activities that can increase concern for the environment among campus students. Furman [37] states that elements of concern can be nurtured through knowledge, such as talks on the importance of anti-littering behavior on ecosystem quality; conduct recycling programs by placing recycling bins in places easily accessible by students; showing video footage of environmental quality and its effects that can increase students' level of concern; involving students in program cleaning activities in institutional areas; training or seminar [38]; etc.…”
Section: Discussionmentioning
confidence: 99%
“…This idea was getting stronger when Allport (1968) emphasized that attitude is "the most distinctive and indispensable concept in contemporary American social Psychology" (p. 59). Though their ideas were challenged by field researches which disproved the relationship between attitude and behavior, however there were also studies that support their ideas such as the study of Abun (2017) on the relationship between environmental attitude and environmental behavior. His study concluded that there is a relationship between environmental attitude and environmental behavior.…”
Section: Attitude Toward Higher Educationmentioning
confidence: 99%
“…The recent studies conducted by Abun (2018) and Fitzsimmons and Douglas (2005) confirmed the consistency of attitude and behavior. Abun (2018) measured the relationship between environmental attitude and environmental behavior and the study found that environmental attitude predicted the environmental behavior of the students and employees toward the environment. Further, he also conducted a study on the entrepreneurial attitude and future intention to establish a business and the finding also indicated a correlation.…”
Section: Attitude Is Key Predictor To Behaviormentioning
confidence: 71%
“…The idea of culture and its effect on brain functioning indicates the power of culture over the formation of the mind and ideas of people about everything around them (Abun, 2018). Donald's View is similar to what Hofstede as cited by Brown (1995) as he argued that culture is the collective programming of the human mind that distinguishes the members of one human group from those of another.…”
Section: Concept Of Human Attitudementioning
confidence: 99%